Antioxidant and antiproliferative activities of the essential oils from thymbra capitata and thymus species grown in Portugal - Miguel, Maria Graça (2017)
The antioxidant and antiproliferative activities of the essential oils from Thymbra capitata and Thymus species grown in Portugal were evaluated. Thymbra and Thymus essential oils were grouped into two clusters: Cluster I in which carvacrol, thymol, p-cymene, α-terpineol, and γ-terpinene dominated and Cluster II in which thymol and carvacrol were absent and the main constituent was linalool. The ability for scavenging ABTS•+ and peroxyl free radicals as well as for preventing the growth of THP-1 leukemia cells was better in essential oils with the highest contents of thymol and carvacrol. These results show the importance of these two terpene-phenolic compounds as antioxidants and cytotoxic agents against THP-1 cells.